Complete response to talazoparib in patient with pancreatic adenocarcinoma harboring somatic PALB2 mutation: A case report and literature review - Kachmazov, Andrei; Bolotina, Larisa; Kornietskaya, Anna; Kuznetsova, Olesya; Ivanov, Maxim; Fedenko, Alexander (Frontiers in Oncology, 2022)
PARP inhibitors has recently emerged as maintenance treatment option for metastatic pancreatic cancer patients with germline BRCA mutations. However, the possibility of PARP-inhibitors use as a standalone targeted therapy for patients with various homologous repair pathway alterations remains mostly undetermined. Here we report a clinical case of a 56-years-old woman with pancreatic ductal adenocarcinoma harbouring somatic PALB2 mutation. Following disease progression after 10 cycles of FOLFIRINOX chemotherapy and 2 cycles of second-line gemcitabine, she was switched to talazoparib and achieved complete clinical response after 25 months of treatment. Patient remains alive without clinical or radiological signs of disease progression three years after the start of talazoparib with no targeted therapy-related toxicities. This case highlights the role of broad molecular profiling as a window of opportunity to achieve durable response for selected pancreatic cancer patients, while pinpointing our gaps in understanding the whole picture of management of these patients, since a new puzzle element represented by PARP inhibitors was introduced to clinical practice.